2020
DOI: 10.15585/mmwr.mm6919a2
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Postpartum Depressive Symptoms and Provider Discussions About Perinatal Depression — United States, 2018

Abstract: Introduction: Perinatal depression is a complication of pregnancy that can result in adverse maternal and infant outcomes. Screening to identify pregnant and postpartum women with depressive symptoms is recommended to provide diagnosis, treatment, and follow-up care to reduce poor outcomes. Methods: CDC analyzed 2018 data from the Pregnancy Risk Assessment Monitoring System to describe postpartum depressive symptoms (PDS) among women with a recent live birth and to assess whether health care providers asked wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(201 citation statements)
references
References 16 publications
4
194
2
1
Order By: Relevance
“…An analysis of 2018 data from the Pregnancy Risk Assessment Monitoring System found that the prevalence of self-reported PPD symptoms averaged 13.2% and was higher among American Indian/Alaska Native (22.0%), Asian/Pacific Islander (19.2%), and black women (18.2%) than among white women (11.4%). 8 However, PPD symptoms were measured with the Patient Health Questionnaire-2 (PHQ-9) instrument, AND symptoms were not measured, and only 31 states were included. Studies also point to increased PND prevalence among low-income women.…”
Section: Prevalence Of Depression In the Perinatal Periodmentioning
confidence: 99%
“…An analysis of 2018 data from the Pregnancy Risk Assessment Monitoring System found that the prevalence of self-reported PPD symptoms averaged 13.2% and was higher among American Indian/Alaska Native (22.0%), Asian/Pacific Islander (19.2%), and black women (18.2%) than among white women (11.4%). 8 However, PPD symptoms were measured with the Patient Health Questionnaire-2 (PHQ-9) instrument, AND symptoms were not measured, and only 31 states were included. Studies also point to increased PND prevalence among low-income women.…”
Section: Prevalence Of Depression In the Perinatal Periodmentioning
confidence: 99%
“…Poor sleep health is a hallmark of perinatal anxiety and depression and it is almost universally present among severe mood disorders and/or postpartum psychosis (Bhati and Richards 2015;Lawson et al 2015;Okun et al 2018). PPD is the most common post-childbirth complication, occurring in approximately 10-15% of US childbearing women (Bauman et al 2020;Bhati and Richards 2015;Chang et al 2012;Hasin and Grant 2015;Nidey et al 2020); it is associated with numerous negative physical and psychological health outcomes in mothers and infants (Slomian et al 2019). Although the literature regarding differences between rural and urban prevalence of sleep and anxiety/depression is mixed, the social context of rural life (e.g., geographic isolation, social stigma) translates to a greater impact on the lives of rural women and their families (Chang et al 2012).…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…Integrating behavioral health services into rural primary care can also be achieved through increased screening for behavioral health problems (Drake et al 2014) and provider-led discussions of mental health during perinatal appointments (Bauman et al 2020). Additionally, focusing on strengthening social support (Mersky et al 2020) and fostering strong alliances between patients and their health care providers can help improve mental health outcomes for mothers and their families (Batra 2019).…”
Section: Potential Strategies For Improving Sleep Healthmentioning
confidence: 99%
“…onset during pregnancy to up to 4 weeks postpartum reported by the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition [DSM-5] 4 to any depressive disorder within the first postpartum year reported by the World Health Organization [WHO]) 1,[5][6][7][8] . The prevalence estimates for depression symptoms among women queried between 2 and 9 months postpartum were 9.7%-23.5% (average of 13.2%) based on an analysis of the Pregnancy Risk Assessment Monitoring System (PRAMS) data from 31 sites by researchers at the Centers for Disease Control (CDC) 9 . Additionally, among 16 continuously reporting sites, a small but statistically significant increase in depression diagnosis (0.22%) was observed from 2012 to 2018.…”
Section: Introductionmentioning
confidence: 99%